Endovascular treatment of non-dissected ascending aorta disease: a systematic review. (18th September 2017) - Wang, Changtian; Regar, Evelyn; Lachat, Mario; von Segesser, Ludwig K; Maisano, Francesco; Ferrari, Enrico
Summary: Severe ascending aorta disease includes aneurysms, pseudoaneurysms (ascending aorta pseudoaneurysms), penetrating aortic ulcers and Type A aortic dissections. Surgical replacement of the aortic root, ascending aorta or aortic arch is the common treatment for severe ascending aortic disease involving the root, the ascending aorta and/or the arch. Despite good surgical results, there is still a risk for morbidity and mortality following surgery for ascending aorta replacement when elderly patients or patients at high risk for surgery are concerned. Less invasive endovascular treatments for ascending aorta repair are under evaluation, and some reports appeared in the available literature in the last decade. However, clinical series or randomized studies are not yet available, and the use of these techniques is still questionable. In this study, we analysed the outcomes of reported cases of endovascular treatment for ascending aorta disease, excluding Type A aortic dissection. We reviewed reports published until February 2017, and we evaluated the employed technology, the devices, the procedural steps and the outcomes. A total of 26 articles reported 67 patients (mean age 65 ± 17 years) who received endovascular treatment for ascending aorta disease: aneurysms, ascending aorta pseudoaneurysms, penetrating aortic ulcers, intramural haematoma, thrombosis, iatrogenic coarctation and aortic rupture. Complications included endoleak (9 cases), stroke (3 cases), non-ST-elevation myocardial infarction (1 case) and splenic infarction (1 case). Three patients required conversion to open surgery, and 1 patient underwent endovascular reintervention. Early mortality was 2.9%. As an alternative treatment for ascending aorta disease in selected high-risk patients, the endovascular repair will gain popularity, but further analysis is required.